Blockade of epidermal growth factor and its receptor and axial elongation in experimental myopia. Issue 10 (16th August 2020) - Dong, Li; Shi, Xu Han; Li, Yi Fan; Jiang, Xue; Wang, Ya Xing; Lan, Yin Jun; Wu, Hao Tian; Jonas, Jost B.; Wei, Wen Bin
Abstract: To examine the influence of epidermal growth factor (EGF) and its receptor (EGFR) on axial ocular elongation, we intraocularly injected an EGF antibody and an EGFR antibody into young guinea pigs with lens‐induced axial elongation (myopization). Mean axial elongation was reduced in the eyes injected with the EGF/EGFR‐antibody compared with the contralateral control eyes injected with PBS (phosphate‐buffered solution) (0.43 ± 0.13 mm vs 0.53 ± 0.13 mm; P  < .001). The intereye difference in axial length increased ( P  = .005) as the doses of the EGF antibody and EGFR antibody increased. As a corollary, the thickness of the retina at the posterior pole was dose‐dependently increased in the injected eyes compared to the contralateral control eyes. Immunohistochemical staining for EGF and the relative mRNA expression of EGF and EGFR were the highest in eyes not injected with the EGF antibody or EGFR antibody and decreased ( P  < .05) as the dose of EGF antibody or EGFR antibody increased. In an in vitro study, EGF had a stimulating effect and the EGF antibody had an inhibitory effect on the proliferation and migration of RPE cells. The findings showed that the intravitreal application of an EGF antibody and EGFR antibody is associated with a dose‐dependent reduction in lens‐induced axial elongation in young guinea pigs. The EGFR family may play a role in axial elongation of the eye and in the development of myopia.